Modelo regulatório da liberação comercial de plantas geneticamente modificadas no Brasil: existe um consenso? / Regulatory model of the commercial release of genetically modified crops in Brazil: is there a consensus? - Denise Gallo Pizella; Marcelo Pereira de Souza; Moacyr Lobo da Costa Jr. (Sociedade & Natureza)
The commercial release of genetically modified crops (GM crops) is an issue of discussion and controversy among different sectors of civil society and experts in the environmental area in relation to its cultivation on a commercial scale, given the potential social, environmental and economic impacts that may ensue over time. This paper examines the issue through questionnaires together with the various actors involved directly or indirectly to the subject, to detect the existing views on the commercial release of GM crops in Brazil. The results show the diversity of opinion among the agents interviewed, but converge to a common need for revision of the Brazilian regulatory model of GM crops with regard to its institutional aspects and the environmental tools used for evaluation prior the commercial release.